Total Quality Management in Education: Strengthening Academic Excellence at MAN 1 Lombok Timur - zarkasi (Innovative Pedagogy and Education Studies, 2024)
This study examines the implementation of Total Quality Management (TQM) in improving the quality of educators and educational staff at MAN 1 Lombok Timur. The research aims to analyze how TQM principles—such as continuous improvement, faculty development, and administrative efficiency—contribute to maintaining high educational standards. A qualitative research approach with a descriptive method was employed, utilizing observations, interviews, and document analysis to gather comprehensive data. The findings indicate that MAN 1 Lombok Timur has successfully implemented TQM by enhancing teacher training programs, performance evaluations, and institutional management systems. The integration of technology in teaching, structured teamwork, and quality control mechanisms has significantly improved teaching effectiveness and student learning outcomes. However, challenges remain, including resistance to change among educators, varying levels of teacher motivation, and financial constraints. Addressing these challenges requires strategic planning, ongoing professional development, and stakeholder engagement to sustain TQM implementation. This study concludes that TQM is an effective model for improving educational quality and can serve as a framework for other Islamic educational institutions seeking to enhance their teaching and administrative practices. To ensure the long-term sustainability of quality education, the study suggests continuous training, stronger stakeholder involvement, and diversified funding sources as key strategies for strengthening TQM implementation at MAN 1 Lombok Timur.